Influenza viral mRNA contains internal N6-methyladenosine and 5'-terminal 7-methylguanosine in cap structures. - Krug, R M (1976)
Influenza viral complementary RNA (cRNA), i.e., viral mRNA was radioactive when purified from the cytoplasmic fraction of cordycepin-treated canine kidney cells that were incubated with [methyl-3H]methionine during infection. Approximately 55 to 60% of the methyl-3H radioactivity was in internal N6-methyladenosine, a feature distinguishing this mRNA from those viral mRNA's that are known to be synthesized in the cytoplasm. The remaining methyl-3H radioactivity was in 5'-terminal cap structures that consisted of 7-methylguanosine in pyrophosphate linkage to 2'-o-methyladenosine, N6, 2'-O-dimethyladenosine, or 2'-O-methylguanosine. Methylated adenosine was the predominant penultimate nucleoside in caps, suggesting that cRNA synthesis in infected cells initiates preferentially with adenosine at the 5' end. In contrast to cRNA, influenza virion RNA segments extracted from purified virus contained mainly 5'-terminal ppA and no detectable cap structures.